(untitled) (Revista da Faculdade de Odontologia - UPF, 2025)
This literature review aimed to explore and synthesize evidence regarding effective behavioral, sensory, and technological interventions in the dental care of children with Autism Spectrum Disorder (ASD). A scoping review was conducted according to the PRISMA protocol. The search was performed in the PubMed, Scopus, and Web of Science databases. Studies evaluating behavioral strategies, sensory adaptations, and assistive technologies in dental settings for children with ASD were included. The selected articles were analyzed thematically, focusing on clinical outcomes and practical feasibility. Out of 74 articles initially identified, 15 met the inclusion criteria. Behavioral interventions such as video modeling and social stories proved effective in reducing anxiety and enhancing patient cooperation. Sensory-adapted environments helped lower physiological and behavioral stress levels. Assistive technologies, including mobile applications, facilitated patient interaction and adherence to treatment. Structured protocols that combined caregiver training with visual pedagogy significantly improved cooperation during dental procedures. The analyzed interventions demonstrate the potential of personalized strategies to meet the specific needs of children with ASD, fostering inclusive and humanized oral healthcare. However, limitations such as small sample sizes and the absence of longitudinal studies highlight the need for future research to refine and validate these approaches across diverse clinical contexts.